A Systematic Review of Family and Media Research (With Emphasis on Virtual Social Networks, Cinema, and Television( - Seyed javad Hosseini; hassan bashir; mozhgan oroji (زن در فرهنگ و هنر)
Families, as crucial social institutions, play a vital role in providing emotional and physical support to their members and teaching life skills. The rapid evolution of communication technologies and media has significantly influenced this institution, leading to major changes within it. This research aims to categorize issues and offer suggestions for addressing gaps in research or media policy-making. The research question is: How have studies in the field of family and the media been classified, and what topics have been discussed under each classification? The theoretical framework of this article is based on Dependency Theory, Manuel Castells' Theory, and Cultivation Theory, with data analysis conducted using meta-analysis and thematic analysis methods. In this study, after reviewing 93 extracted articles on the subject of media and family, and analyzing descriptive statistics and themes in areas such as social networks, television, and cinema, the strengths and weaknesses of the research were identified. The results indicate that the effects of modernity and media on the family institution in Iran have been profound and multifaceted. These value changes include the removal of traditions, weakening of kinship relations, empowerment of women, increased importance of individualism, and changes in lifestyles. These transformations represent a period of cultural and social transition, emphasizing the need to focus on the Iranian-Islamic lifestyle, the identity of men and women, strengthening family cohesion and relationships, media literacy, and attention to the role and position of children and adolescents within the family.